Hydrodynamic Modeling of Water-Entry of the Wedge Shape with Considering Asymmetric Impact - Ghassemi, Hassan; Rayatpisheh, Ali; Ta’abbodi, Navid (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
The slamming of the planing crafts is the most important structural phenomenon that a vessel is encountered during their career. Many researchers have investigated this phenomenon in various methods. In this paper we investigated the analytical results of impact of symmetrical wedge to the water surface briefly, then the asymmetric impact of a 2D section of a wedge to the water surface was studied. To analyze above phenomenon, we used a numbers of analytical relationships that summarizes how to achieve these equations. Finally, obtained analytical relationships were used to determine the pressure distribution and maximum value on a wedge with different deadrise angles. The results indicated good agreement between the obtained results and results of other researcher’s studies.